Hepatic Arteriolosclerosis: A Small-vessel Complication of Diabetes and Hypertension. (July 2015) - Balakrishnan, Maya; Garcia-Tsao, Guadalupe; Deng, Yanghong; Ciarleglio, Maria; Jain, Dhanpat
Abstract : Liver involvement in diabetes is well recognized in the form of steatohepatitis and glycogenic hepatopathy. More recently, sinusoidal fibrosis, even in the absence of steatosis, has also been suggested to be associated with diabetes (diabetic hepatosclerosis); however, case-control studies are lacking. In addition, microangiopathy (hyaline arteriolosclerosis), a well-known complication of diabetes, has not been well studied in liver. Therefore, we undertook a cross-sectional blinded study with the specific aim of evaluating the association between hepatic sinusoidal fibrosis and hepatic arteriolosclerosis (HA) with diabetes. Liver biopsy findings from 89 diabetic patients obtained between January 2006 and December 2009 were compared with those of 89 nondiabetic patients matched by age and hepatitis C virus infection status. Patients with cirrhosis, liver mass, right heart failure, significant alcohol use, or insufficient available clinical information were excluded. Medical records were reviewed for the presence of diabetes, body mass index, diabetes treatment, and comorbidities at the time of biopsy (eg, underlying liver disease, hypertension, dyslipidemia). Liver biopsies were evaluated blinded to all clinical data (including presence or absence of diabetes) for a variety of histologic features, especially patterns of fibrosis and HA. Diabetic patients had a higher average body mass index (33 vs. 30 m/kg 2, P =0.0039), prevalence of hypertension (78% vs. 33%, P <0.0001), and dyslipidemia (52% vs. 20%, P <0.0001). Among diabetic patients, 87% had type 2 diabetes, and 57% used insulin. Whereas sinusoidal fibrosis, with or without steatosis, was not significantly associated with the presence of diabetes, HA was significantly more prevalent among diabetic patients compared with controls: 45% versus 29% ( P =0.0298). The presence of both diabetes and hypertension had a significant odds for HA: with an adjusted odds ratio of 2.632 (95% confidence interval, 1.178-5.878; P =0.0183). Biliary changes were associated with HA in some cases (10.6%).In this study, we describe the histopathologic entity of HA for the first time. It is a small-vessel complication (microangiopathy) of the liver observed mainly in patients with diabetes who also have arterial hypertension. The clinical and prognostic implications of this finding, particularly regarding liver injury, remain to be further investigated.